Lipid parameters in non-moderate and prolonged drinking of alcohol - Gautam, MP; Ghimire, U; Gurung, KB; Guruprasad, S; Subramanyam, G (Journal of College of Medical Sciences-Nepal, 2012)
Alcohol consumption in moderate amount is cardio-protective and its beneficial effect is largely mediated through its impact on cholesterol; however the impact of non-moderate drinking on lipid parameters has not been evaluated. This study was designed to assess the effect of non-moderate and prolonged drinking on various lipid values. Fifty non-moderate drinkers (>25 g/day for last 10 years) were selected and lipid profile measurement was done at fasting state and findings were analyzed and the level was correlated with life time intake amount. Mean daily intake, duration and life time intake amount of alcohol were 64.3 g, 22 years and 502 kg respectively. Only 4 % and 16% alcohol users had high and borderline high total cholesterol respectively. Majority (72 %) has optimal level of HDL and only 22 % and 6 % had low and high level respectively. Similarly, majority alcohol users (80 %) had desired level of total cholesterol. Only 38 % alcoholic subjects had normal, others, 20 % and 40 % had either borderline high or high triglyceride level respectively. Regarding the LDL, majority has optimal (60 %) or near optimal (38 %), only 2 % had borderline high level. Similarly, regarding non-HDL, only 12 % subjects had high and majority (88 %) had optimal level. In correlation analysis, the relation between lifetime intake amount and these lipoprotein levels was inconclusive. In conclusion, the prolonged and non-moderate drinking was associated with mostly optimal and desired level of various lipid parameters. The only undesirable effect of alcohol consumption was the high triglyceride level that was recorded in majority. However, the correlation of the levels of these lipoproteins with life time intake was inconclusive. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5961 JCMSN 2011; 7(1): 1-11